Labour market marginalisation in obsessive–compulsive disorder: a nationwide register-based sibling control study. Issue 6 (28th June 2018) - Pérez-Vigil, Ana; Mittendorfer-Rutz, Ellenor; Helgesson, Magnus; Fernández de la Cruz, Lorena; Mataix-Cols, David
Abstract: Background: The impact of obsessive–compulsive disorder (OCD) on objective indicators of labour market marginalisation has not been quantified. Methods: Linking various Swedish national registers, we estimated the risk of three labour market marginalisation outcomes (receipt of newly granted disability pension, long-term sickness absence and long-term unemployment) in individuals diagnosed with OCD between 2001 and 2013 who were between 16 and 64 years old at the date of the first OCD diagnosis ( n = 16 267), compared with matched general population controls ( n = 157 176). Hazard ratios (HR) with 95% confidence intervals (CI) were calculated using Cox regression models, adjusting for a number of covariates (e.g. somatic disorders) and stratifying by sex. To adjust for potential familial confounders, we further analysed data from 7905 families that included full siblings discordant for OCD. Results: Patients were more likely to receive at least one outcome of interest [adjusted HR = 3.63 (95% CI 3.53–3.74)], including disability pension [adjusted HR = 16.36 (95% CI 15.34–17.45)], being on long-term sickness absence [adjusted HR = 3.07 (95% CI 2.95–3.19)] and being on long-term unemployment [adjusted HR = 1.72 (95% CI 1.63–1.82)]. Results remained similar in the adjusted sibling comparison models. Exclusion of comorbid psychiatric disorders had a minimal impact on the results. Conclusions: Help-seeking individuals with OCD diagnosed in specialist care experience marked difficulties to participate in the labour market. The findings emphasise the need for cooperation between policy-makers, vocational rehabilitation and mental health services in order to design and implement specific strategies aimed at improving the patients' participation in the labour market.